Local Government Policy in Improving Human Development Index in the Education in Bone Regency - M. Awaluddin A (Jurnal Ilmiah Ilmu Administrasi Publik, 2022)
This study aims to analyze local government policies in increasing the human development index in the education sector and to find out what factors are inhibiting and supporting the Education Office in increasing the human development index in Bone Regency. This research is descriptive in nature with a qualitative explanation. Data collection was carried out by interviewing observation and documentation, then data analysis was carried out through data reduction, data verification and drawing conclusions. The Bone Regency Education Office in increasing the education index number has carried out various things including the nine-year compulsory education program, non-formal education programs and programs to improve the quality of education staff and education staff. In its implementation, the Education Office has done everything possible and has shown good results, although there are still deficiencies.